Necrotizing sialometaplasia: systematic review and meta analyses over the past 46 years - Néri, Júlia dos Santos Vianna; Silva, Viviane Palmeira da; Araújo, Nara Santos; Gomes, Thiago Alexsander Oliveira; Nascimento, Mayana Barreto do; Cangussu, Maria Cristina Teixeira; Ramalho, Luciana Maria Pedreira; Santos, Jean Nunes dos (Journal of Oral Diagnosis, 2024)
Objectives: The aim of this study was to characterize the main characteristics of this disease in relation to diagnosis, clinical aspects, progression and treatment as well as correlating them with remission time. Material and Methods: A systematic search was performed following the guidelines given by PRISMA and the Joanna Briggs Institute. PubMed, Web of Science and Scopus were the databases used. Results: The final analysis resulted in 108 articles with 173 clinical cases. The longest remission time for signs and symptoms (>7 weeks) was registered among male patients (p = 0.02) and outside the oral cavity; however no significant correlation was observed (p>0.05). A high risk of bias was the most common rating among the articles analyzed (55%); followed by moderate (27%) and low (18%). The lack of standardization in clinical case report descriptions made it difficult to gain a thorough knowledge of the essential characteristics of the NS pathological processes. Conclusion: It is recommended that publications follow the standards recommended by the literature; in addition, studies using advanced technologies to better understand NS’s pathological path are recommended so as to propose effective treatments for this disease.